Concise Review: The Endothelial Cell Extracellular Matrix Regulates Tissue Homeostasis and Repair. (11th December 2018) - Witjas, Franca M. R.; van den Berg, Bernard M.; van den Berg, Cathelijne W.; Engelse, Marten A.; Rabelink, Ton J.
Abstract: All tissues are surrounded by a mixture of noncellular matrix components, that not only provide physical and mechanical support to cells, but also mediate biochemical signaling between cells. The extracellular matrix (ECM) of endothelial cells, also known as the perivascular matrix, forms an organ specific vascular niche that orchestrates mechano-, growth factor, and angiocrine signaling required for tissue homeostasis and organ repair. This concise review describes how this perivascular ECM functions as a signaling platform and how this knowledge can impact the field of regenerative medicine, for example, when designing artificial matrices or using decellularized scaffolds from organs. Stem Cells Translational Medicine 2019;8:375–382 :